Optimization of a circular microchannel heat sink using entropy generation minimization method - Jafari, Arash (2009)
New advances in micro and nano scales are being realized and the contributions of micro and nano heat dissipation devices are of high importance in this novel technology development. Past studies showed that microchannel design depends on its thermal resistance and pressure drop. However, entropy generation minimization (EGM) as a new optimization theory stated that the rate of entropy generation should be also optimized. Application of EGM in microchannel heat sink design is reviewed and discussed. Using EGM, majority of the published investigations are conducted based on rectangular cross section microchannel. Latest principles for deriving the entropy generation correlations are discussed to present how this approach can be achieved. The present study involves an optimization procedure using EGM method and derives the entropy generation rate in circular microchannel heat sink based upon thermal resistance and pressure drop simultaneously. The equations are solved using MATLAB and the obtained results are compared to the past studies. The effect of channel diameter and number of channels on the entropy generation rate, Reynolds number, thermal resistance and pressure drop is investigated. Analytical correlations are utilized for heat transfer and friction coefficients. A minimum entropy generation has been observed for N=40 and channel diameter of 9090µm. It is concluded that for N=40 and channel hydraulic diameter of 9090µm, the circular microchannel heat sink is on its optimum operating point based on second law of thermodynamics.